(untitled) - Box, George E P. (New Jersey, 1994)
This book is concened with the building of stochastic (statistical) models for time series and their use in important areas of application. This includes the topics of forecasting, model specification, estimation, and checking, transfer function modeling of dynamic relationships, modeling the effects of intervention events, and process control.
Keywords: Feedback control systems,Prediction theory,Time-series analysis,Transfer functions; Mathematical models